CHARACTERISTICS OF THE YOGURT BEING INCUBATED IN GREEN COCONUT SHELL (Cocos nucifera L. var. viridis Hassk) - M. R. R, TATTU; LINDAWATI, S. A.; MIWADA, I N. S. (Majalah Ilmiah Peternakan; Vol 24 No 1 (2021): Vol. 24 No. 1 (2021), 2021)
The study aims to identify characteristics of the yogurt being incubated in green coconut shell (Cocos nucifera L. var. viridis Hassk). It was conducted in March 2020 at the Laboratory of Animal Product Technology and Mic- robiology Faculty of Animal Science, Udayana University. This studies used a Complete Random Design (CDR) with three treatments and five replications. The three treatments were incubated in a jar container (control) (P0), incubated in green coconut shell nonflesh (P1) and incubated in green coconut shell with flesh (P2). The variables observed were lactoce level, fat level, protein level and pH value. The results of this study have shown that yogurt’s characteristic indicated lactose and protein levels was not significantly different (P>0,05) in all treatments, but P2 fat levels was higher significantly (P<0,05) different than P1 and P0. pH values was not significantly different (P>0,05) with P1 and significantly different (P<0,05) with P0. Conclusing in this study that the characteristics of yogurt incubated in green coconut shell getting good results at lactose level 2,32,42%; fat level 10,60-12,50%; pro- tein level 4,80-4,90%; and value pH 4,14-4,24%.